2016
DOI: 10.18632/oncotarget.10141
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 expression in hepatocellular carcinoma cells is associated with tumor progression

Abstract: IL-35 has recently been demonstrated to play significant roles in the progression of various malignant tumors. We investigated the expression of IL-35 in hepatocellular carcinoma (HCC) and the regulatory mechanisms in HCC progression. Tissue microarray from 75 HCC patients revealed that IL-35 was primarily localized in the cytoplasm of cancer cells and peri-tumoral hepatocytes. Quantitative analysis showed that IL-35 expression was significantly lower in patients in the advanced stages than in the early stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
(35 reference statements)
2
39
1
Order By: Relevance
“…Interleukin-35 (IL-35) is a newly discovered member of the interleukin family with anti-inflammatory and immune inhibitory effects [7,8]. Recently, it has been demonstrated that IL-35 plays an important role in tumor progression, including lung cancer [9], pancreatic cancer [10], nasopharyngeal carcinoma [11], gastric cancer [12], hepatocellular carcinoma [13][14][15], breast cancer [16,17], renal cell carcinoma [18] and colorectal cancer [19,20]. However, the underlying mechanisms of IL-35 in NSCLC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-35 (IL-35) is a newly discovered member of the interleukin family with anti-inflammatory and immune inhibitory effects [7,8]. Recently, it has been demonstrated that IL-35 plays an important role in tumor progression, including lung cancer [9], pancreatic cancer [10], nasopharyngeal carcinoma [11], gastric cancer [12], hepatocellular carcinoma [13][14][15], breast cancer [16,17], renal cell carcinoma [18] and colorectal cancer [19,20]. However, the underlying mechanisms of IL-35 in NSCLC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21,23,26,72 Although a majority of investigations points to IL-35 as a cytokine promoting tumor growth and metastasis, 8,10,15,53,61,71 there is one evidence suggesting IL-35 acting as anti-cancer cytokine 24 and another one suggesting IL-35 as a factor limiting tumor metastasis. 61 Moreover, it was reported that accumulation of CD39 1 Foxp31 Treg cells and enhanced IL-35 in hepatocellular carcinoma (HCC) samples was associated with HCC aggressiveness and recurrence after resection. 60 CD39 is an extracellular ectonucleoside triphosphate diphosphohydrolase-1 enzyme that catalyzes the conversion of extracellular ATP to adenosine, being the latter a suppressor of effector T cell functions.…”
Section: Il-35 and Cancermentioning
confidence: 99%
“…73 In contrast to these findings, in another study, it was also shown that IL-35 expression was significantly lower in HCC in advanced stages than in early disease. 61 Studies in vitro have revealed that overexpression of IL-35 in HepG2 hepatic cell line was associated with several effects such as, reduced matrix metalloproteinase-2 (MMP2) and MMP9 activities, restriction of cell migration ability, as well as upregulation of MCH class I and CD95 death receptor on the cell surface of cancer cells. 61 These effects may explain the reported antimetastatic activity of IL-35 in HCC (Fig.…”
Section: Il-35 and Cancermentioning
confidence: 99%
“…Improving immune cells function with cytokine thera- 15 Despite these conflicting data, IL-35 remains a potential and promising study target in HCC.…”
Section: Immune System In Hepatocellular Carcinomamentioning
confidence: 99%